2010
DOI: 10.1038/ncb2102
|View full text |Cite
|
Sign up to set email alerts
|

O2 regulates stem cells through Wnt/β-catenin signalling

Abstract: Stem cells reside in specialized microenvironments or “niches” which regulate their function. In vitro studies employing hypoxic culture conditions (≤ 5% O2) have revealed strong regulatory links between O2 availability and stem/precursor cell functions1–6. Therefore, while some stem cells are perivascular, others may occupy hypoxic niches and be regulated by O2 gradients. However, the underlying mechanisms remain unclear. Here, we show that Hypoxia Inducible Factor-1α (HIF-1α), a principal mediator of hypoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
395
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 421 publications
(415 citation statements)
references
References 33 publications
18
395
2
Order By: Relevance
“…In these studies, Hif-1␣ interacted with ␤-catenin via its NH 2 terminus and thereby inhibited the interaction of ␤-catenin with TCF4. However, the regulation of Wnt/␤-catenin signaling may be cell-and differentiation stage-specific as Hif-1 was recently reported to enhance canonical Wnt signaling in embryonic stem cells but to have no effect on the pathway in neuroprogenitor cells (57). Finally, it should be noted that other factors including FoxO1 (58) and NMP4-CIZ (12) have also been shown to modulate ␤-catenin activity in osteoblasts, with the actions of the latter being responsive to experimental loading.…”
Section: Discussionmentioning
confidence: 99%
“…In these studies, Hif-1␣ interacted with ␤-catenin via its NH 2 terminus and thereby inhibited the interaction of ␤-catenin with TCF4. However, the regulation of Wnt/␤-catenin signaling may be cell-and differentiation stage-specific as Hif-1 was recently reported to enhance canonical Wnt signaling in embryonic stem cells but to have no effect on the pathway in neuroprogenitor cells (57). Finally, it should be noted that other factors including FoxO1 (58) and NMP4-CIZ (12) have also been shown to modulate ␤-catenin activity in osteoblasts, with the actions of the latter being responsive to experimental loading.…”
Section: Discussionmentioning
confidence: 99%
“…Certain studies have suggested that HIF-1α activation regulates the Wnt/β-catenin signaling pathway, which activates the expression of target genes and contributes to the enhanced invasion of hypoxic gastric cancer cells (35)(36)(37). CD44 is a target gene of the Wnt/β-catenin signaling pathway (38); therefore, the mechanism by which HIF-1α regulates CD44 may be associated with the Wnt/β-catenin signaling pathway in gastric cancer.…”
Section: Discussionmentioning
confidence: 99%
“…promoters that enhance tumor survival [446]. Strikingly, the promoters of genes of Tcf-1 and Lef-1contain hypoxia response elements (HREs) [451] and Hif-1 is directly involved in regulating Tcf/Lef protein abundance [451]. Hif-1 also is involved in regulating the transcription of proteins implied the destruction complex, and has been shown to negatively regulate the transcription of APC via hypoxia-responsive elements, which could lead to increased cellular -catenin levels.…”
Section: The -Catenin Tcf/lef Transcription Complexmentioning
confidence: 99%